Uno Dental Card Game as an Effort to Improve Dental Health Knowledge in Elementary School Students - Tsakila, Siti Qoulan; Purnama, Tedi (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: along with the development of technology, technology-based educational learning media has also developed, one of which is the uno card application. Elementary school children need appropriate and adequate educational learning media to increase their knowledge, especially regarding health, especially dental and oral health, the formation of a fun learning situation is also one way to achieve ideal and meaningful learning. The presence of media, especially visual media in learning activities, will help foster the initial interest of respondents which is expected to be able to stimulate further curiosity about the material being taught. Objective: To analyze the effectiveness of dental health knowledge before and after being given dental health education with the uno dental card media game for elementary school children. Method: The research design used in this study was a quasi-experiment with a pretest and posttest design with one group design. This study was conducted in March-April 2024 on grade 5 students of SDN 08 Cilandak Barat. The instruments used include a questionnaire and the uno dental card media game. Data analysis is conducted using the Wilcoxon test. Results: The results of this study indicate that the average value of knowledge about dental health maintenance before being given education with the Uno dental card media game is 90.73 and after being given education with the Uno dental card media game is 97.80 with a good category, with the Wilcoxon test results of p <0.001. Conclusion: The Uno dental media game is effective in increasing knowledge about dental and oral health as evidenced by an increase in the average value of knowledge which is included in the good criteria or this can be seen from the difference in the average value of knowledge of 7.71 which means an increase